1978
DOI: 10.1056/nejm197806082982303
|View full text |Cite
|
Sign up to set email alerts
|

The Relations between Structural Changes in Small Airways and Pulmonary-Function Tests

Abstract: To examine the relation between small-airways abnormalities and specific lung functions, we performed pulmonary-function tests in 36 patients, of whom two were nonsmokers, one to three days before open-lung biopsy for localized pulmonary lesions. The primary lesion in the small airways was a progressive inflammatory reaction leading to fibrosis with connective-tissue deposition in the airway walls. Increase in disease in small airways correlated with deterioration in lung function. Lesions could be reliably de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
412
2
24

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 761 publications
(454 citation statements)
references
References 13 publications
16
412
2
24
Order By: Relevance
“…4). This observation is very similar to that previously reported in human smokers [3] where the small airways (i.e., internal diameter <2 mm) were found to be affected, primarily by airway fibrosis and inflammatory infiltrate. Table 1 shows that both cigarette smoke exposed groups had a smaller weight gain than the Control group, the average of CS and CS+NAC groups amounting to 75% of the weight gain of the Control animals.…”
Section: Morphometrysupporting
confidence: 91%
See 1 more Smart Citation
“…4). This observation is very similar to that previously reported in human smokers [3] where the small airways (i.e., internal diameter <2 mm) were found to be affected, primarily by airway fibrosis and inflammatory infiltrate. Table 1 shows that both cigarette smoke exposed groups had a smaller weight gain than the Control group, the average of CS and CS+NAC groups amounting to 75% of the weight gain of the Control animals.…”
Section: Morphometrysupporting
confidence: 91%
“…The phase III slope of the N 2 single breath washout (SBW) test became a popular index of small airways alteration since the work by COSIO et al [3] showed its correlation with morphological scores of small airways abnormalities in smokers with normal spirometry. A later SBW study by VAN MUYLEM et al [4], which included helium and sulphur hexafluoride tracer concentrations, also revealed distinct correlations between indices derived from He and SF 6 slopes and airway pathology scores.…”
mentioning
confidence: 99%
“…In addition, the putative role played by TGF-1 in airway wall thickening in asthma has been recently proposed in a study showing that levels of TGF-1 are increased in BAL fluid of asthmatic patients at baseline and after local allergen challenge [31]. In chronic bronchitis, airway wall fibrosis has also been demonstrated [32,33]. The elevated levels of TGF-and FN released by AM from patients with chronic bronchitis may be of importance in the regulation of fibrosis, since airways macrophages are increased in numbers in the bronchial mucosa [13].…”
Section: Discussionmentioning
confidence: 99%
“…COPD is caused by the noxious effects of tobacco smoke, which leads to airway epithelial injury and the induction of changes such as squamous metaplasia (SM), the reversible replacement of the normal columnar epithelium by squamous epithelium (6). In 1978, Cosio et al noted that SM correlated with the severity of airway obstruction, suggesting that SM and airway obstruction may be linked (7).…”
Section: Introductionmentioning
confidence: 99%